The Role of Green HRM in Optimizing Management Performance in Umrah Travel Companies : Literature Review in Umrah Travel - Destry Febrian, Wenny; Hamidah Sari, Ovi (Dinasti Publisher, 2024)
This article is expected to provide valuable insights for industry practitioners, policymakers, and academics in understanding the dynamics of implementing sustainable practices in this unique service sector. This article uses a qualitative method by using a literature review as the basis in this scientific article or as a data source. This method allows researchers to gain an in-depth understanding of how Green HRM is applied in the specific context of Umrah travel companies in Jakarta and its impact on management performance. This qualitative approach is suitable for exploring complex and contextual phenomena such as the implementation of Green HRM in specific industries. With a combination of the implementation of Green HRM and improved management performance, Umrah tour and travel companies in Jakarta can achieve sustainability and sustainable growth in the long term.